2013
DOI: 10.1016/j.earlhumdev.2012.07.012
|View full text |Cite
|
Sign up to set email alerts
|

Sex and gestational age effects on auditory brainstem responses in preterm and term infants

Abstract: Background Some studies find delayed development of the auditory brainstem in preterm infants, but others do not. Aim To compare auditory brainstem responses (ABRs) in healthy preterm and term infants depending on sex and gestational age (GA). Methods Participants were 111 preterm (27–36 weeks GA) and 92 term (37–41 weeks GA) infants. ABR tests were conducted at 6 weeks (corrected age if preterm). Results There were no overall differences between term and preterm groups in ABRs. However, males showed lon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 31 publications
0
12
0
1
Order By: Relevance
“…In contrast, the use of BAEP, studies show differences in relation to gender. A study consisted of 111 preterm and 92 full term showed higher absolute latency of components I, III and V and their interpeaks in the male gender (17) . Another study with BAEP verified lower responses in females, when compared to males, for term newborns, except for the component I and higher latency values for females in preterm infants (15) .…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…In contrast, the use of BAEP, studies show differences in relation to gender. A study consisted of 111 preterm and 92 full term showed higher absolute latency of components I, III and V and their interpeaks in the male gender (17) . Another study with BAEP verified lower responses in females, when compared to males, for term newborns, except for the component I and higher latency values for females in preterm infants (15) .…”
Section: Discussionmentioning
confidence: 92%
“…The CAEP has its use as a maturational biomarker of the auditory pathway, due to decrease of exogenous components latency over the first years of life (6) . Differences in latency and amplitude of components were studied in different age groups through the LLAEP (2,4,7,8,9,10,11) or BAEP (12,13,14,15,16,17,18) .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, premature female infants have also been shown to have maturational advantage, specifically with auditory neural maturation. (53) These may explain our finding of better language outcomes in girls compared to boys. Similarly, our finding of significant association between chronic lung disease with Auditory Comprehension and not with Expressive Communication is consistent with similar previously reported finding in premature infants.…”
Section: Discussionmentioning
confidence: 75%
“…In addition, ASD and ABRs exhibit sex differences. ASD affects 4–5 males per female (Centers for Disease Control 2014), and males produce longer ABR latencies for all major wave components across the lifespan (Jerger and Hall 1980, Li, Zhu et al 2013). ASD and ABRs are also sensitive to perinatal health risks and exhibit family resemblance (Jiang 1998, Jerger, Chmiel et al 1999, Maziade, Merette et al 2000, Jiang, Brosi et al 2005).…”
Section: Introductionmentioning
confidence: 99%